Development of web-based three tier multiple choice test to measure student's tree thinking; try out. (April 2020) - Julaeha, S; Hidayat, T; Rustaman, N Y
Abstract: Development of three tier multiple choice tests were conducted to detect and measure of student's tree thinking on classification concept. Three tier multiple choice test was developed with web integration of a Google Classroom application for easy feedback. The study involved a number of high school students (n = 29) who had studied the concept of Animal Classification. The research procedure was carried out through stages: literature study, problem analysis, and instrument design. The instrument was validated by expert and analyze using ANATES version 4.0. Tree thinking was measured on the basis of identification of evolutionary characters, phylogenetic relationships, concept of clade, MRCA (Most Recent Common Ancestor), sister groups, tree topologies, number of evolutionary changes, and sequence of evolution in species. The validation results show that the three tier multiple choice test can be used to measure students' tree thinking. In addition, the results analysis of items with ANATES version 4.0 indicated that the test has high reliability (r = 0.69), very good of differences (D> 0.4) on 12 items, and difficult on 14 items. This study show that 11 test items were directly accepted (60%), 3 items were accepted but with revision (15%), 4 items were rejected (25%). The conclusion obtained from this study was that the web-based three-tier multiple choice test developed was good and can be used to measure of student's tree thinking.